Cost‐Effectiveness of Paclitaxel‐Coated Balloon Angioplasty in Patients With Drug‐Eluting Stent Restenosis. Issue 7 (17th April 2013) - Dorenkamp, Marc; Boldt, Julia; Leber, Alexander W.; Sohns, Christian; Roser, Mattias; Boldt, Leif‐Hendrik; Haverkamp, Wilhelm; Bonaventura, Klaus
Abstract Background The economic impact of drug‐eluting stent (DES) in‐stent restenosis (ISR) is substantial, highlighting the need for cost‐effective treatment strategies. Hypothesis Compared to plain old balloon angioplasty (POBA) or repeat DES implantation, drug‐coated balloon (DCB) angioplasty is a cost‐effective therapy for DES‐ISR. Methods A Markov state‐transition model was used to compare DCB angioplasty with POBA and repeat DES implantation. Model input parameters were obtained from the literature, and the cost analysis was conducted from a German healthcare payer's perspective. Extensive sensitivity analyses were performed. Results Initial procedure costs amounted to €3488 for DCB angioplasty and to €2782 for POBA. Over a 6‐month time horizon, the DCB strategy was less costly (€4028 vs €4169) and more effective in terms of life‐years (LYs) gained (0.497 versus 0.489) than POBA. The DES strategy incurred initial costs of €3167 and resulted in 0.494 LYs gained, at total costs of €4101 after a 6‐month follow‐up. Thus, DCB angioplasty was the least costly and most effective strategy. Base‐case results were influenced mostly by initial procedure costs, target lesion revascularization rates, and the costs of dual antiplatelet therapy. Conclusions DCB angioplasty is a cost‐effective treatment option for coronary DES‐ISR. The higher initial costs of the DCB strategy compared to POBA or repeat DES implantation are offset by later cost savings.